Water Treatment using Moringa Oleifera as Natural Coagulation and Flocculation - Samriya, J R; Chavda, P D; Patel, D B; Patel, P M; Nehal, Chavda; Sherasiya, Misba; Saha, Sweta (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Moringa Oleifera is a tropical plant whose seeds contain an edible oil and water-soluble substance, which has excellent coagulation properties for treating water and wastewater. The efficiency and properties of Moringa Oleifera as a natural coagulant in water treatment were studied and compared with alum, which is presently the most widely used industrial coagulant. As India grows and urbanizes, its water bodies are getting toxic. Major ill health, which affects humanity especially in the developing countries, can be trace to lack of safe and wholesome water supply. It estimated that around 70% of surface water in India is unfit for consumption. Every day, almost 40 million liters of wastewater enters rivers and other water bodies with only a tiny fraction adequately treated. The cost to clean rivers and providing reliable water is too expensive. Moringa Oleifera can be used as a coagulant for primary treatment of water. The use of local seeds Moringa Oleifera to improve the quality of drinking water. Moringa Oleifera has been compared to alum in its effectiveness as a purifying agent of water, but with a major advantage, because it can be produced locally, the effectiveness of the seeds may vary from one to another. Two different location's water samples were collected from Dantiwada Dam, Banaskantha District, Gujarat (India) which serves as a source of drinking water and irrigation in the surrounding rural area. After experiment, we conclude that we can use Moringa Oleifera as a primary treatment; it effective method to treat water at lowest cost in developing country like India.